Assessment of volume reduction of uterus and uterine fibroids using arterial embolization - Singh, Gurmit Kaur a/p Sardara (2006)
Objective: The objective ofthis study was to assess the volume reduction ofthe uterus and the uterine fibroid using artery embolization for patients with symptomatic fibroids. This study was also aimed to determine the complications of uterine artery embolization and to document improvement ofthe symptoms post UAE. Materials and Methods: Twelve patients had bilateral uterine artery embolization(UAE) for symptomatic uterine fibroids. This study was conducted over a period of 21 months in Hospital Universiti Sains Malaysia. All the patients had a pre-embolization Magnetic Resonance Imaging (MRI) and ten of the patients had a repeat MRI three months post uterine artery embolization. One patient developed bleeding post-embolization and had a hysterectomy done. The second patient got pregnant immediately post-embolization and delivered a healthy term baby girl by caesarean section. Volume of the uterus and the dominant fibroid was calculated pre-embolization and post-embolization. Comparison was done between the volume pre-embolization and post-embolization, to see the percentage of reduction. Symptom improvement and the complication due to uterine artery embolization were also noted. Results Results show fibroid volume reduction median to be 63.82% with interquartile range of 36.78 and uterine volume reduction median to be 47.85% with interquartile range of 36.99. Symptom improvement at three months was 85-100%. The complications which occurred were mostly minor complications with one major complication requiring hysterectomy. Conclusion: UAE is an effective and a safe method of treatment for symptomatic uterine fibroids. There is significant symptom and volume reduction of both the uterus and the dominant fibroid.